2022
DOI: 10.1039/d2cp02440c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model for moisture-controlled CO2 sorption

Abstract: The understanding of the sorption/desorption kinetics is essential for practical applications of moisture-controlled CO2 sorption. We introduce an analytic model of the kinetics of moisture-controlled CO2 sorption and its interpretation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The energy cost of moisture-swing carbon capture has been reported as 50 kJ/mol . As a result, in the past decade, there has been growing interest in the use of ion-exchange resins (IERs) for moisture-swing carbon capture: materials that capture CO 2 under dry conditions and release it under humid conditions. , There have also been recent advances on a conceptually different but related, continuous, moisture-gradient-assisted capture process. , These systems consume minimal energypotentially even relying on natural humidity gradientsand exhibit rapid kinetics as well as reliable, cyclic performance at ambient CO 2 levels …”
Section: Introductionmentioning
confidence: 99%
“…The energy cost of moisture-swing carbon capture has been reported as 50 kJ/mol . As a result, in the past decade, there has been growing interest in the use of ion-exchange resins (IERs) for moisture-swing carbon capture: materials that capture CO 2 under dry conditions and release it under humid conditions. , There have also been recent advances on a conceptually different but related, continuous, moisture-gradient-assisted capture process. , These systems consume minimal energypotentially even relying on natural humidity gradientsand exhibit rapid kinetics as well as reliable, cyclic performance at ambient CO 2 levels …”
Section: Introductionmentioning
confidence: 99%
“…The chemical reaction of CO 2 with primary amines (RNH 2 ) comprises two sequential elementary reactions. 5,16 The first step leads to the formation of carbamic acids (RNHCOOH) as:…”
Section: Co 2 Capture By Primary Secondary and Tertiary Aminesmentioning
confidence: 99%
“…In the 2000s, it was experimentally observed that the CO 2 affinity of a strong-base anion exchange resin is affected by humidity levels, which points to the presence of moisture-swing or moisture-controlled CO 2 sorption. [13][14][15][16] In this system, CO 2 is sorbed when the sorbent is dry, and CO 2 is desorbed when the sorbent is wet. [17][18][19] Interestingly, such a negative correlation between water and CO 2 sorption in quaternary ammonium is opposite to co-absorption observed in primary amines or secondary amines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DAC researchers have studied the applicability of a variety of materials with quaternary ammonium groups for the moisture swing sorption process. However, comprehensive investigations are still required to better understand the mechanism, develop faster kinetics, increase the loading capacity, and enhance the selectivity for CO 2 . Porous polymers, ammonium-based anion exchange resins, ammonium-functionalized ionic liquids, cellulose and chitosan/PVA aerogels, ammonium-modified silica, colloidal crystal templates, and sorbent-containing electrospun fibers have been evaluated as sorbents. , He and co-workers tested three QA-functionalized porous materials and reported CO 2 uptake between 0.13 and 0.49 mmol/g when cycling the relative humidity between 20 and 95% .…”
Section: Introductionmentioning
confidence: 99%